Russia in a Changing World: the Continuity of the Priorities and New Opportunities - V. V. Putin (MGIMO University Press, 2012)
Speech of the President of the Russia Vladimir Putin at the Meeting of the Russian Ambassadors and Permanent Representatives Abroad at the Ministry for Foreign Affairs of Russia, 9 july 2012.